Blood Pressure Profile and Trends in the Neonatal Transitioning Period: A Comparative Study of Term Asphyxiated and Healthy Newborns - Adekunle Bamidele Taiwo FWACP; John Akintunde Okeniyi FWACP; Olatunde Ezra Ogundare FWACP; Odunayo Adebukola Fatunla FWACP; Olarinre Adefunke Babatola FWACP; Oyeku Akibu Oyelami FWACP (SAGE Publishing, 2022)
Background . Extra-uterine transition difficulties including BP abnormalities have been documented following perinatal asphyxia. Aim . The study aimed to determine the BP changes in the early neonatal transitioning period. Method . This comparative, cross-sectional study was conducted at the Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria. Result. A total of 246 term babies were analyzed. Their mean (standard deviation) systolic, diastolic and mean arterial blood pressures (SBP, DBP, and MBP) at birth were 68.2 (9.0), 39.9 (7.0), and 49.4 (6.9) mmHg and 67.4 (7.9), 37.1 (6.1), and 47.2 (5.8) mmHg, respectively. Asphyxiated neonates had significantly higher initial DBP ( P < .001) and MAP ( P = .008), lower SBP ( P < .001) and MAP ( P = .024) at 6 hours and lower SBP at 12 hours after birth, statistically. Conclusion . This study showed that while the BP of healthy neonates steadily increases in the first 48 hours after birth, it fluctuated markedly within the first 12 hours of birth among asphyxiated babies.